Immature stages and new host plant records for eight euptychiine butterflies in southeastern Peru (Lepidoptera: Nymphalidae: Satyrinae: Satyrini) - Nakahara, Shinichi; Vega, Yeison; Corahua-Espinoza, Thalia; Kabir, Jamal; Maclure, Calum; Duerr, Nathan; Gallice, Geoffrey; Cervantes-Martinez, Joselin; Arteaga, Zunilda Escalante; Tejeira, Rafael; Ccahuana, Rodrigo; Baine, Quinlyn (Zootaxa, 2026)
We here report the immature stages and novel host plant records for six species in the nymphalid subtribe Euptychiina, which are documented based on populations found in the Madre de Dios department, Peru: Caeruleuptychia urania (Butler, 1867), Harjesia blanda (Möschler, 1876), Deltaya ocypete (Butler, 1867), Yphthimoides renata (Stoll, 1780), Cisandina philippa (Butler, 1867), Cisandina castanya Lamas & Nakahara, 2022. We also report new host plant records for two euptychiine species: Magneuptychia libye (Linnaeus, 1767) and Modestia harpyia (C. Felder & R. Felder, 1867). A total of eight euptychiine species are discussed in the present study and the majority of new host plant records for them belong to the family Poaceae except for M. harpyia which was found feeding on seedlings of Euterpe precatoria (Arecaceae). We provide photos of documented immature stages and host plants for species discussed herein, as well as DNA barcode data for selected taxa.